Properties of Anoxybacillus sp. 3M Xylanases and further application towards sugar rich hydrolysates - Alves, Luís (2015)
This study aimed to optimize the production of xylanases by Anoxybacillus sp. strain 3M, a thermophilic bacterium isolated from terrestrial hot springs (temperature of 90°C) samples collected on S. Miguel, Azores, Portugal, in batch fermentation testing several agroindustrial byproducts as inducer substrates (BSG - Brewer's spent grain, wheat straw, sugarcane bagasse, and corn cobs). In addition, the xylanases produced by this bacterium with the best inducer substrate were characterized for their optimal pH, temperature and stability. The results for xylanase production showed that the higher levels of xylanases were obtained in growth medium containing 1% (w / v) BSG (1.35 U/mL), but the xylanolytic activity was also observed when wheat straw (1.32 U/mL), sugarcane bagasse (0.80 U/mL), corn cobs (0.30 U/mL) and commercial xylan (0.21 U/mL) were used as substrates. The extracellular crude enzymatic extract from Anoxybacillus sp. 3M was then characterized for its optimal temperature and pH and stability. The best enzyme activity was observed at a temperature of 60 ºC and pH 5.3, and the enzyme retained 100% of its original activity after 96 h at 60 °C and pH 7.0. Zymogram of native gel analysis of the different culture supernatants revealed the presence of an enzyme complex with a molecular weight of 420 kDa. This xylanase may be considered as a biocatalyst thermotolerant and it is interesting for biotechnological applications. Further application of Anoxybacillus 3M crude enzymatic extract to BSG and commercial xylan revealed the presence of xylose and xylooligosaccharides, mainly X2 and X3, in the hydrolizates produced.